Synthesis and Antimicrobial Evaluation of a New Series of N-1, 3-Benzothiazol-2-ylbenzamides. (1st October 2013) - Armenise, Domenico; Carocci, Alessia; Catalano, Alessia; Muraglia, Marilena; Defrenza, Ivana; De Laurentis, Nicolino; Rosato, Antonio; Corbo, Filomena; Franchini, Carlo
Abstract : Enterococcus faecalis is a Gram-positive commensal inhabitant of the intestinal tract of humans, animals, and insects. However, it is also an opportunistic pathogen and has emerged as a leading cause of hospital-acquired extraintestinal infections. Fluoroquinolones have been frequently used to treat E. faecalis infections, and the emergence of fluoroquinolone-resistant E. faecalis strains has recently been reported in several countries. Thus, the identifications of new antibiotics specifically directed to E. faecalis may be envisaged. In this paper, a new series of N -1, 3-benzothiazol-2-ylbenzamides have been designed, synthesized, and evaluated for their in vitro antimicrobial activities. Among the tested compounds, 3i was active against E. faecalis .